Vaccine‐induced immune thrombotic thrombocytopenia (VITT) – a novel clinico‐pathological entity with heterogeneous clinical presentations. (22nd June 2021) - Lavin, Michelle; Elder, Patrick T.; O'Keeffe, Denis; Enright, Helen; Ryan, Eileen; Kelly, Anna; El Hassadi, Ezzat; McNicholl, Feargal P.; Benson, Gary; Le, Giao N.; Byrne, Mary; Ryan, Kevin; et al.
Summary: Vaccine‐induced immune thrombotic thrombocytopenia (VITT) is a novel entity that emerged in March 2021 following reports of unusual thrombosis after ChAdOx1 nCoV‐19, (AstraZeneca) vaccination. Following the recognition of this syndrome, multiple consensus guidelines have been released to risk stratify patients presenting with possible symptoms after ChAdOx1 nCoV‐19 vaccination. All guidelines rapidly identify VITT in patients with the complete triad of thrombocytopenia, thrombosis and elevated D‐dimers after ChAdOx1 nCoV‐19 vaccination. However, with earlier recognition of the associated symptoms, the clinical manifestations are likely to be more heterogeneous and represent an evolving spectrum of disease. In this setting, current guidelines may lack the sensitivity to detect early cases of VITT and risk missed or delayed diagnoses. The broad clinical phenotype and challenges associated with diagnosis of VITT are highlighted in our present case series of four patients with confirmed VITT. Dependent on the guidance used, each patient could have been classified as a low probability of VITT at presentation. The present study highlights the issues associated with the recognition of VITT, the limitations of current guidance and the need for heightened clinical vigilance as our understanding of the pathophysiology of this novel condition evolves.